The decomposition method for linear, one-dimensional, time-dependent partial differential equations - D. Lesnic (International Journal of Mathematics and Mathematical Sciences)
The analytical solutions for linear, one-dimensional, time-dependent partial differential equations subject to initial or lateral boundary conditions are reviewed and obtained in the form of convergent Adomian decomposition power series with easily computable components. The efficiency and power of the technique are shown for wide classes of equations of mathematical physics.